S80. Utility of reduced montage EEG in detecting seizures or seizure-like activity. (May 2018) - Gururangan, Kapil; Razavi, Babak; Parvizi, Josef
Abstract : Introduction: Standard scalp EEG is used to detect a wide range of cerebral pathologies. However, its utility in emergency and resource-limited settings may be impeded by delays in setup and interpretation. Past studies have investigated reduced channel arrays as screening tools, but inferred a lower utility in detecting epileptiform abnormalities. The current study tested the utility of reduced (8-channel) montage (rm-EEG) covering the lateral hemispheres compared to full (18-channel) montage (fm-EEG) for detection of generalized and hemispheric seizures and seizure-like patterns by neurologists with extensive EEG training, neurology residents with minimal EEG training, and medical students without EEG training. Methods: Forty neurologists (7 epileptologists, 13 epilepsy fellows, 20 neurology residents) from 7 institutions and 42 medical students from Stanford University were presented 44 samples of EEG recordings (15-s long) as both fm-EEG and rm-EEG formats in a random order. Samples represented seizures ( n  = 8), seizure-like activity (lateralized or generalized periodic discharges or burst suppression, n  = 12) or non-rhythmic, non-periodic patterns (normal or slowing, n  = 24) as determined by majority agreement among 3 senior epileptologists with >10 years of training (Fleiss' kappa 0.79). Both physicians and students were asked to determine whether each sample represented seizure activity (yes/no), while epileptologists and residents were also asked to specify any and all pathological activity present in each sample. We calculated the overall accuracy of fm-EEG and rm-EEG, as well as their sensitivity and specificity for seizures and seizure-like activity; differences were assessed using paired t -tests. Results: EEG samples were evaluated with almost identical accuracy using fm-EEG (epileptologists: 88%; residents: 75%; students: 57%) and rm-EEG (epileptologists: 84%, p  = 0.156; residents: 75%, p  = 0.086; students: 57%, p  = 0.461). While epileptologists identified hemispheric or generalized seizure activity with high sensitivity using fm-EEG (99%) and rm-EEG (94%, p  = 0.172), individuals with minimal or no EEG experience demonstrated lower sensitivity using rm-EEG (residents: 79%; students: 45%) compared to fm-EEG (residents: 91%, p  = 0.031; students: 62%, p  = 0.048). However, specificity for seizures/seizure-like activity was greater using rm-EEG (epileptologists: 91%; residents: 84%; students: 73%) compared to fm-EEG (epileptologists: 85%, p  = 0.015; residents: 77%, p  = 0.018; students: 63%, p  < 0.001). Conclusion: Our study demonstrates that a reduction from 18 to 8 channels does not degrade the sensitivity for generalized and hemispheric seizures, and yet provide more specific information for ruling in such epileptic activity even when read by individuals with minimal or no EEG experience. On the basis of these findings, we suggest that a restricted channel configuration can be used for faster diagnosis of generalized and hemispheric seizures that ought to be detected and treated expeditiously.